Studi Pelayanan Jemput Bola Akta Kelahiran Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Lingga - Agus Piranda; Zulkifli Zulkifli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
This study aims to determine the level of objective of the Lingga Regency Population and Civil Registration Service Public Service (Service Study of Birth Certificate). Indicators for evaluating public services include, service procedures, time of completion, service costs, service products, facilities and facilities, competency of officers. This type of research located in Lingga Regency, Riau Islands Province is a descriptive survey which prioritizes questionnaires as a means of collecting data and collected data with this tool and then becomes the main raw material for analyzing empirical conditions of the objective objectives of research objectives at meticulous locations. the population and sample in the community research using 14 birth certificate pick-up services. sampling technique used for the community using insindetal sampling techniques. The types and techniques of data collection consist of primary data collected by questionnaire and interview techniques and secondary data using techniques. Based on this analysis, the researcher concluded that the public service of the district population office and civil registration (the study of picking up birth certificate services at intervals is quite good. Recommendations that need to be considered especially regarding procedures and time of improvement that must be improved again so that the community is satisfied with the delivery service) ball given.